Analysis of the Influenza Epidemic in 2016 and Pandemic in 2009 Based on Two National Centers of WHO in the Russian Federation - L. S. Karpova; N. M. Popovtseva; T. P. Stolyarova; K. A. Stolyarov; A. A. Sominina; E. I. Burtseva (Эпидемиология и вакцинопрофилактика)
Goal of the work - comparison of the epidemic process in the epidemic of 2016 and during the 2009 pandemic in the cities of Russia. Comparative data of the incidence of influenza and acute respiratory viral infections, hospitalization and mortality in different age groups of children (0 - 2, 3 - 6 and 7 -14 years) and adults (15 - 64 and 65 years of age) from 59 cities collaborating with 2 National Centers for influenza to the WHO in Russia, for the period from the 2009 pandemic and epidemic 2016. For the epidemic of 2016, as the 2009 pandemic was characterized by mono etiology (influenza virus A(H1N1)pdm09, the simultaneous occurrence of the peak of the epidemic in all age groups, the same percentage admitted to hospital with a diagnosis of "influenza"; involvement of the adult population and school children in the cities. The epidemic of 2016 was different: less involvement of children up to 6 years, higher development rate, the spread on the territory of Russia - from the West to the East, shorter duration of the epidemic in the country (12 and 17 weeks) and in the cities by population average (4.6 and 6.8 weeks), less morbidity for the period of the epidemic in cities (5.4 and 8.5%) and the country (9.6 and 14.4%), greater frequency of hospitalization but lower mortality from influenza in an average of 1.7 times.